2011
DOI: 10.1177/1545109710393309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Depression and Coping Skill among HIV-Positive People in Kolkata, India

Abstract: The objectives of the present study were to evaluate depressive symptoms and coping strategy among HIV-positive women and men. This cross-sectional study was done among 164 newly diagnosed HIV-positive people through a structured questionnaire. Beck Depression Inventory (BDI) scale was used to measure depression. A 16-items coping scale, Coping with AIDS - Fleishman (CWAF) Instrument, was used to assess coping strategy. χ(2) test was used to compare proportions. Men had significantly higher mean BDI somatic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(11 reference statements)
3
7
0
Order By: Relevance
“…A positive coping strategy was associated with a lower expressed need for the support of a CHW or a patient support group at the same point in time. This is in line with previous studies demonstrating that positive coping strategies were related to higher levels of adherence [ 55 ] and better mental health [ 56 ], signifying the fact that these patients are adapting to their situation well and do not necessarily require additional support measures. In addition, the seeking social support coping style was associated with a higher probability of wanting the support of a CHW.…”
Section: Discussionsupporting
confidence: 91%
“…A positive coping strategy was associated with a lower expressed need for the support of a CHW or a patient support group at the same point in time. This is in line with previous studies demonstrating that positive coping strategies were related to higher levels of adherence [ 55 ] and better mental health [ 56 ], signifying the fact that these patients are adapting to their situation well and do not necessarily require additional support measures. In addition, the seeking social support coping style was associated with a higher probability of wanting the support of a CHW.…”
Section: Discussionsupporting
confidence: 91%
“…Both types of social support were leveraged by women with moderate to severe depression and anxiety, who reported that both social and financial support from family, friends and colleagues mitigated their mental distress (68). In contrast to the typical Western view of women as more emotion-focussed, Talukdar found that women in India engaged in problem-focused coping more frequently than men (28). Finally, avoidant coping, represented by our avoidant emotions factor, has been consistently observed in Indian populations, including sero-positive women in discordant partnerships in Bangalore (27), depressed patients in Jaipur, Rajasthan (69), and women with high levels of felt stigma and/or AIDS symptoms in rural South India (29).…”
Section: Discussionmentioning
confidence: 80%
“…Other cross-cultural studies revealed high prevalence rates of depression in HIV population, namely 67 % in China [41], 34 % in Portugal [42], 56 % in India [43], and 53.5 % in Brazil [44].…”
Section: Epidemiology Of Depression In Hiv-infected Patientsmentioning
confidence: 97%